Vietnam : Selected Issues. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper analyzes performance of the Vietnamese economy during the 1990s. It reviews recent monetary and banking developments, and provides an assessment of the main problems in the banking sector. The paper highlights that during the late 1990s, Vietnam's banking sector came under mounting pressure from the slowdown in growth and the weakening financial position of state-owned enterprises. In addition, problems emerged from banks' large foreign exchange exposure, accumulation of nonperforming loans, weak capital base, and low profitability.